Epigenetics in cardiac disease - Backs, Johannes; McKinsey, Timothy A. (Springer, 2016)
This book describes important advances in our understanding of how environmental conditions affect cardiac gene expression through epigenetic mechanisms. Further, it discusses the roles of chromatin modifications (in particular DNA methylation and histone modifications) and of chromatin regulators in the context of cardiac diseases. The book provides readers with an overview of our current understanding of epigenetic regulation in the heart, and will stimulate further research in this exciting field. Edited and written by internationally respected experts, it addresses the needs of professors, students and researchers working in the fields of cardiac biology and epigenetics
Keywords: Epigenetik; Herzkrankheit